2021
DOI: 10.5851/kosfa.2020.e102
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance (NMR)-Based Quantification on Flavor-Active and Bioactive Compounds and Application for Distinguishment of Chicken Breeds

Abstract: The purpose of this study was to use 1 H nuclear magnetic resonance ( 1 H NMR) to quantify taste-active and bioactive compounds in chicken breasts and thighs from Korean native chicken (KNC) [newly developed KNCs (KNC-A, -C, and -D) and commercial KNC-H] and white-semi broiler (WSB) used in Samgye. Further, each breed was differentiated using multivariate analyses, including a machine learning algorithm designed to use metabolic information from each type of chicken obtained using 1 H-13 C heteronuclear single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In addition, the variable importance in projection ( VIP ) score was calculated, which expresses the importance of the variables for the discrimination of groups in PLS-DA. Metabolites with VIP scores higher than 1.0 were considered to be the major contributors to the formation of the PLS-DA model ( Kim et al, 2021b ). In our study, the VIP scores were calculated to evaluate the importance of individual metabolites in separating CB and WB in PLS-DA and how they changed during 7 d of refrigerated storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the variable importance in projection ( VIP ) score was calculated, which expresses the importance of the variables for the discrimination of groups in PLS-DA. Metabolites with VIP scores higher than 1.0 were considered to be the major contributors to the formation of the PLS-DA model ( Kim et al, 2021b ). In our study, the VIP scores were calculated to evaluate the importance of individual metabolites in separating CB and WB in PLS-DA and how they changed during 7 d of refrigerated storage.…”
Section: Resultsmentioning
confidence: 99%
“…The content of some nucleotide-related products (hypoxanthine, IMP, inosine, and UMP) in chicken breast was also affected by refrigerated storage. As enzymatic reaction occurs after slaughter, IMP breaks down, with the simultaneous accumulation of inosine and hypoxanthine in fresh meat ( Kim et al, 2021b ). Similarly, UMP can also be decomposed into nucleosides and nucleobases by the catalytic reaction of 5’-nucleotidase during cold storage ( Dong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The NMR analysis was performed according to Kim et al (2021) [29]. In brief, each minced sample (5 g) was homogenized with 20 mL of 0.6 M perchloric acid at 12,000 rpm for 1 min (T25 digital ULTRA-TURRAX ® , IKA Co.).…”
Section: Nuclear Magnetic Resonance (Nmr)-based Metabolic Analysismentioning
confidence: 99%
“…Therefore, it is necessary to develop efficient methods to distinguish meat with different breed origins. For this purpose, metabolomics-based approaches were developed and have been applied to discriminate pork [146], chicken [45,168], and duck [43] meat of different breeds. By the NMR-based metabolomics method, the amino acid carnosine was identified as the metabolite most strongly correlated to the sensory attributes of the pork meat from different breeds [146].…”
Section: Species Originmentioning
confidence: 99%
“…Compared with commercial broilers, Korean native chicken meat possesses higher amounts of IMP, α-glucose, lactate, and anserine and lower amounts of free amino acids. A further study reported by Kim et al developed a metabolomics approach based on 2D HSQC analysis to differentiate between Korean native chickens and white-semi broiler, demonstrating superior performance to the conventional quality assessment tools [168].…”
Section: Species Originmentioning
confidence: 99%